Creating associations to substitute banks' direct credit: Evidence from Belgium - Mikel Bedayo (National Bank of Belgium, 2016)
Firms' incentives to join other firms to collectively apply for a unique loan is empirically studied in this paper. When several firms jointly apply for a unique loan an association of firms is created. We identify the associations that had access to credit in Belgium over the period 2001-2011 and the firms that created each association, observing the amount of credit both the firms and the associations obtained from each financial institution they used. We analyze the amount of credit obtained by firms depending on whether they belonged to any association, firms' likelihood to form associations, the impact of belonging to an association on the amount of credit firms' receive from banks, as well as the effect of not obtaining any credit directly on the amount the associations these firms create get. Further, we analyze whether associations formed by common-ownership firms have access to higher amount of credit than the rest of associations. We find that big and old firms are more likely to join other firms to mutually apply for credit and that associations get more credit if all its members use the same bank the association uses to get credit from. Furthermore, the lower firms' credit over the last year the more likely they are to form associations to obtain credit, and we show that associations composed of small firms with no credit history are specially credit constrained.
Keywords: G21; G30; 330; Associations; Finance; Access to credit; Relationship banking; Belgium